AKTIVITAS FISIK ANAK SUKU MENTAWAI - Muhamar Kodafi Putra (Dharmas Journal of Sport, 2022)
People in the Mentawai hinterland depend on physical activity  to meet their daily needs and survival. A person must be physically fit to perform his basic daily tasks efficiently over a relatively long period of time, so that he has spare power for other activities without feeling tired. The purpose of this research is to reveal the form and purpose of the physical activity  of the people in the Mentawai hinterland who are experiencing the process of viability. This research is a qualitative research. Techniques and tools for collecting data from observations, asking questions and making videos or making documentation. The research results are then processed. The results of this study reveal that an activity that produces sweat that is driven by the Mentawai tribe can make them able to live healthily until now. Mentawai people in the interior physically have higher skills and skills than ordinary people in general, which can be compared to someone who does physical exercise every day. Their activities aim to find produce for daily food, while their "outsiders" tend to carry out daily physical activities in order to be fit and achieve. Therefore, it is recommended for sports enthusiasts to utilize and channel the sports abilities of the Mentawai rural community to help fulfill their daily needs.